Strength Estimation of Concrete in Different Environments Using UPV - Jaafar, Mohd Saleh; Thanoon, Waleed Abdulmalik; Mohiuddin Khan, Shibli Russel; Trikha, D. N. (Universiti Putra Malaysia Press, 2002)
Deterioration of concrete in a structure is a result of several internal and external degradation mechanisms which decrease the strength or the integrity of the structure. This paper presents results of use of non-destructive ultrasonic pulse velocity tests (UPV) to determine the strength of concrete in three different environments, namely oven-dry, air-dry and saturated conditions, as the full potential of UPV in different environments is still not fully explored. Moisture is known to have a significant effect on ultrasonic pulse velocity. In order to improve the efficiency of UPV in estimating the concrete strength, the degree of moisture present in the concrete i.e. the physical condition of the concrete is to be considered. Pulse velocity path in the different physical conditions of concrete also has to be examined. In the present investigations, four different grades of concrete in three different environments were considered. Extensive series of tests were carried out in the laboratory to obtain a correlation of the UPV test results with the actual compressive strength of concrete. A total of 108 cubes were cast. The cement used was the ordinary Portland cement and the coarse aggregate consisted of granite with the maximum aggregate size of 19mm as is generally used in conventional RC structures. The DOE-method of mix-design was used to design four different grades of concrete in order to simulate concrete strengths found in practice. Test results indicated that the presence of moisture in concrete changes the UPV values significantly. The UPV tests through the direct transmission measurements display better estimates compared to the indirect measurements. Exponential expressions have been proposed for the strength estimation of concrete under oven dry and air dry conditions.